2013
DOI: 10.3109/0142159x.2013.774332
|View full text |Cite
|
Sign up to set email alerts
|

The transition to hospital consultant: Denmark and the Netherlands compared on preparedness for practice, perceived intensity and contextual factors

Abstract: The importance of contextual aspects in the transition is underscored and shows that Denmark appears to succeed better in aligning training with practice. Regulations regarding working hours and progressive independence of trainees appear to facilitate the transition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 35 publications
3
33
0
Order By: Relevance
“…In the research headed by Jonne van der Zwet on GP supervisors in an undergraduate setting we showed that differences between cultures, in this case general practice as opposed to clinical care, are even used by supervisors to ''privilege certain practical, social, and professional activities or values'' (van der Zwet et al 2014). In a comparative study between Denmark and the Netherlands, we looked at social and cultural variations between these two countries to explain the finding that new Danish consultants perceived their transition into a first position as consultant to be less intensive, and reported less burnout than their Dutch counterparts (Westerman et al 2013b). My participation in these studies, and the gradual conceptualisation of the ETR framework, has taught me how omnipresent social and cultural reifications are.…”
Section: Level 3: Recurrent Activities Results In Social and Cultural mentioning
confidence: 97%
“…In the research headed by Jonne van der Zwet on GP supervisors in an undergraduate setting we showed that differences between cultures, in this case general practice as opposed to clinical care, are even used by supervisors to ''privilege certain practical, social, and professional activities or values'' (van der Zwet et al 2014). In a comparative study between Denmark and the Netherlands, we looked at social and cultural variations between these two countries to explain the finding that new Danish consultants perceived their transition into a first position as consultant to be less intensive, and reported less burnout than their Dutch counterparts (Westerman et al 2013b). My participation in these studies, and the gradual conceptualisation of the ETR framework, has taught me how omnipresent social and cultural reifications are.…”
Section: Level 3: Recurrent Activities Results In Social and Cultural mentioning
confidence: 97%
“…Medical students' preparedness for practice as junior doctors can be improved by prior experiential, work-based learning in clinical practice during their medical programme (Brennan et al 2010). There are a number of ways in which the nature of learning in clinical placements can influence preparedness for practice (Westerman et al 2013;Tokuda et al 2010). For example, early clinical exposure allows medical students to 'actup' as junior doctors and may ease their transition to internship (Brennan et al 2010;Hauer et al 2012;Daly et al 2013a); At the same time failure to be prepared for practice can have negative consequences.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Wilkie and Raffaeli [8] state that each transition involves a ‘fundamental re-examination of who and what we are, even if this processing is occurring at a largely unconscious level’. More specifically, in the transition from speciality training to hospital consultant, new consultants find themselves confronted with, and often overwhelmed by, a host of new challenges, such as final responsibility for patient care and novel non-clinical tasks relating to financial, leadership and management responsibilities [9, 10]. As a result, new consultants are forced to rapidly respond and adapt to these new circumstances and job requirements.…”
Section: Four Reflections On the Concept Of Callingmentioning
confidence: 99%